Changes in muscle power after usual care or early structured exercise intervention in acutely hospitalized older adults. Issue 4 (10th March 2020) - Sáez de Asteasu, Mikel L.; Martínez‐Velilla, Nicolás; Zambom‐Ferraresi, Fabricio; Ramírez‐Vélez, Robinson; García‐Hermoso, Antonio; Cadore, Eduardo L.; Casas‐Herrero, Álvaro; Galbete, Arkaitz; Izquierdo, Mikel
Abstract: Background: A classic consequence of short‐term bed rest in older adults is the significant loss in skeletal muscle mass and muscle strength that underlies the accelerated physical performance deficits. Structured exercise programmes applied during acute hospitalization can prevent muscle function deterioration. Methods: A single‐blind randomized clinical trial conducted in an acute care for elders unit in a tertiary public hospital in Navarre (Spain). Three hundred seventy hospitalized patients [56.5% female patients; mean age (standard deviation) 87.3 (4.9) years] were randomly allocated to an exercise intervention ( n = 185) or a control ( n = 185) group (usual care). The intervention consisted of a multicomponent exercise training programme performed during 5–7 consecutive days (2 sessions/day). The usual‐care group received habitual hospital care, which included physical rehabilitation when needed. The main endpoints were change in maximal dynamic strength (i.e. leg‐press, chest‐press, and knee extension exercises) and maximal isometric knee extensors and hip flexors strength from baseline to discharge. Changes in muscle power output at submaximal and maximal loads were also measured after the intervention. Results: The physical exercise programme provided significant benefits over usual care. At discharge, the exercise group showed a mean increase of 19.6 kg [95% confidence interval (CI), 16.0, 23.2; P < 0.001] on the one‐repetition maximum (1RM) in the leg‐press exercise, 5.7 kg (95% CI, 4.7, 6.8; P < 0.001) on the 1RM in the chest‐press exercise, and 9.4 kg (95% CI, 7.3, 11.5; P < 0.001) on the 1RM in the knee extension exercise over usual‐care group. There were improvements in the intervention group also in the isometric maximal knee extension strength [14.8 Newtons (N); 95% CI, 11.2, 18.5 vs. −7.8 N; 95% CI, −11.0, −3.5 in the control group; P < 0.001] and the hip flexion strength (13.6 N; 95% CI, 10.7, 16.5 vs. −7.2 N; 95% CI, −10.1, −4.3; P < 0.001). Significant benefits were also observed in the exercise group for the muscle power output at submaximal loads (i.e. 30% 1RM, 45% 1RM, 60% 1RM, and 75% 1RM; all P < 0.001) over usual‐care group. Conclusions: An individualized, multicomponent exercise training programme, with special emphasis on muscle power training, proved to be an effective therapy for improving muscle power output of lower limbs at submaximal loads and maximal muscle strength in older patients during acute hospitalization.